Lenalidomide, melphalan, and prednisone, followed by lenalidomide maintenance, improves health-related quality of life in newly diagnosed multiple myeloma patients aged 65 years or older: Results of a randomized phase III trial - Dimopoulos, M.A.; Delforge, M.; Hájek, R.; Kropff, M.; Petrucci, M.T.; Lewis, P.; Nixon, A.; Zhang, J.; Mei, J.; Palumbo, A. (Haematologica, 2013)
The MM-015 trial assessed the effect of lenalidomide-based therapy on health-related quality of life. Patients (n=459) with newly diagnosed multiple myeloma aged 65 years or over were randomized 1:1:1 to nine 4-week cycles of lenalidomide, melphalan, and prednisone, followed by lenalidomide maintenance; or lenalidomide, melphalan, and prednisone, or melphalan and prednisone, with no maintenance therapy. Patients completed health-related quality of life questionnaires at baseline, after every third treatment cycle, and at treatment end. Health-related quality of life improved in all treatment groups during induction therapy. Patients receiving lenalidomide maintenance had the most pronounced improvements, Global Health Status/Quality of Life (P<0.05), Physical Functioning (P<0.01), and Side Effects of Treatment (P<0.05) out of 6 pre-selected health-related quality of life domains. More patients receiving lenalidomide maintenance achieved minimal important differences (P<0.05 for Physical Functioning). Therefore, lenalidomide, melphalan, and prednisone, followed by lenalidomide maintenance, improves health-related quality of life in patients with newly diagnosed multiple myeloma. (Clinicaltrials.gov identifier NCT00405756). © 2013 Ferrata Storti Foundation.